(untitled) - Holze, Rudolf (Weinheim, Germany, 2009)
The only comprehensive collection of easy-to-perform electrochemical experiments for both high school lessons and university lab courses. It illustrates the broad area of electrochemistry with respect to thematic aspects and apparatus used in the experiments. In addition, it highlights the interdisciplinary connections to related fields. Following a brief overview, the book goes on to deal with electrochemistry at equilibrium and with flowing current, while further chapters cover analytical electrochemistry, non-traditional methods, electrochemical energy storage and conversion as well as technical electrochemistry. Throughout, the author clearly describes every detail of the experiments and gives helpful guidance for the production of rare working materials. Complementing textbooks on electrochemistry, this is a must for lecturers as well as for students in chemistry.
Keywords: Electrochemistry,Electrochemistry; Laboratory manuals